The Beneficial Effect of Hypnosis in Elective Cardiac Surgery: A Preliminary Study - Akgul, Ahmet; Guner, Beyhan; Çırak, Musa; Çelik, Derya; Hergünsel, Oya; Bedirhan, Sevim (The Thoracic and Cardiovascular Surgeon, 2016)
Background Single-session hypnosis has never been evaluated as a premedication technique in patients undergoing coronary artery bypass grafting (CABG). The aim of the present study was to evaluate the beneficial effects of clinical hypnotherapy on perioperative anxiety, pain perception, sedation, and necessity for ventilator assistance in patients undergoing CABG.Methods Double-blind, randomized, clinical trial was performed. Forty-four patients undergoing CABG surgery were randomized into two groups. The patients in group A received preprocedural hypnosis by an anesthesiologist. Patients in group B (control) had only information on the surgical intervention by the same anesthesiologist. State-Trait-Anxiety Index-I (STAI-I) and Beck Depression Inventory (BDI) were performed preoperatively in both groups. Visual analog scale (VAS) and Ramsay sedation scale (RSS) were evaluated on 0th, 1st, 2nd, 4th, 6th, 8th, 10th, 12th, and 24th hours, postoperatively. Postoperative anxiety level, analgesic drug consumption, and duration of ventilator assistance and intensive care unit (ICU) stay were also documented.Results When anxiety and depression levels were compared, significantly lower STA-I and BDI values were detected in group A after hypnotherapy (p = 0.001, p = 0.001, respectively). Significantly less total doses of remifentanil (34.4 ± 11.4 vs. 50.0 ± 13.6 mg) and morphine (4.9 ± 3.3 vs. 13.6 ± 2.7 mg) were administered in group A in the postoperative period. Ventilator assistance duration (6.8 ± 2.0 vs. 8.9 ± 2.7 hours) was also shorter in group A when compared with that in group B (p = 0.007).Conclusion Hypnosis session prior to surgery was an effective complementary method in decreasing presurgical anxiety, and it resulted in better pain control as well as reduced ventilator assistance following CABG surgery.
Keywords: coronary artery bypass grafts surgery; pharmacology; quality of life